2019
DOI: 10.2147/cmar.s195726
|View full text |Cite
|
Sign up to set email alerts
|

<p>Total pancreatectomy compared with pancreaticoduodenectomy: a systematic review and meta-analysis</p>

Abstract: Aim: To assess whether total pancreatectomy (TP) is as feasible, safe, and efficacious as pancreaticoduodenectomy (PD). Materials and Methods: Major databases, including PubMed, EMBASE, Science Citation Index Expanded, Scopus and the Cochrane Library, were searched for studies comparing TP and PD between January 1943 and June 2018. The meta-analysis only included studies that were conducted after 2000. The primary outcomes were morbidity and mortality. Pooled odds ratios (ORs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…Further, 9% of patients with malignant IPMN would be treated as low risk, and their diagnoses would be missed [ 12 , 13 , 14 ]. Conversely, pancreaticoduodenectomy and total pancreatectomy are relatively invasive treatments with treatment-related mortalities of 0–4.9% and 0–8%, respectively, and they require careful indication [ 15 , 16 , 17 ]. Additional malignant predictors, including new biomarkers, are required to select an optimal treatment for IPMN.…”
Section: Introductionmentioning
confidence: 99%
“…Further, 9% of patients with malignant IPMN would be treated as low risk, and their diagnoses would be missed [ 12 , 13 , 14 ]. Conversely, pancreaticoduodenectomy and total pancreatectomy are relatively invasive treatments with treatment-related mortalities of 0–4.9% and 0–8%, respectively, and they require careful indication [ 15 , 16 , 17 ]. Additional malignant predictors, including new biomarkers, are required to select an optimal treatment for IPMN.…”
Section: Introductionmentioning
confidence: 99%
“…Oncologically, median number of lymph nodes harvested was significantly higher in the TP group 20 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) vs. 15 (11)(12)(13)(14)(15)(16)(17)(18)(19)) (p-0.003). In patients with malignant disease positive resection margins (R1) was observed in 3.4% (n-6) of the patients in the PD group and in 2.9% (n-1) of the TP group (p-0.88).…”
Section: Resultsmentioning
confidence: 94%
“…Hartwig et al published the short and long term outcome of 434 total pancreatectomies for pancreatic and peri-ampullary tumors and concluded that TP is justified by improved survival rates, acceptable quality of life and stable vitamins and HbA1 C levels (11). Currently, no randomized control trials comparing PD with TP have been reported in the English literature, but several retrospective comparative studies and meta-analyses addressed this issue in the past with controversial results (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Patient selection for TP remain a difficult choice and the purpose of the current study is to evaluate weather TP is as feasible and safe as PD in terms of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Массивная кровопотеря во время операции у пожилого, исходно анемизированного пациента с факторами риска, к сожалению, привели через ряд осложнений к неблагоприятному исходу. Несмотря на то что у операции Уиппла по-прежнему высоки показатели послеоперационных осложнений и летальности [13][14][15], наряду с низкими показателями долгосрочной выживаемости [16,17], панкреатодуоденальная резекция показана при любых подозрительных опухолеподобных поражениях периампулярной зоны [6]. Неожиданные результаты окончательного гистологического исследования лишь подчеркивают, что в сомнительных случаях дифференциального диагноза хирургический метод остается золотым стандартом [6].…”
Section: Discussionunclassified